Kepatuhan Petugas Kesehatan Terhadap Standar Pelayanan Antenatal Yang Berkualitas Di Puskesmas Kabupaten Karawang - Maryono Maryono (Pancanaka, 2020)
During 2014 - 2016, the coverage of antenatal services (ANC) in Karawang regency in addition to exceeding the target, this coverage was also above the provincial and national coverage. Although ANC coverage has increased, Karawang district ranks second in West Java with the highest number of maternal deaths. The high ANC coverage results (quantitative), but the still high number of maternal deaths, this shows the still low quality of the ANC in Karawang district. This study aims to determine the description of compliance of health workers in implementing antenatal service standards. The research sites were Rengasdengklok Health Center, Ciampel Health Center, and Jatisari Health Center, Karawang Regency. This research is a type of qualitative research with an ethnographic approach. Data collection is done through observation, documentation, and in-depth interviews. Data analysis uses an interactive method consisting of: data reduction, data presentation and drawing conclusions. The validity of the data uses triangulation techniques, negative case analysis, member checks, and low inference descriptors (verbatim), and peer discussions. The results showed that health workers at the three research centers focused on the policy, facilities and infrastructure, standard operating procedures, and team coordination. Compliance of health workers will be better if there are more adequate policies, complete facilities and infrastructure, clear operational standard procedures, and more team coordination and strong leadership. Keywords: compliance, ANC, quality, supervisi